FC 030CONTACTIN-1 IS A NOVEL ANTIGEN IN IDIOPATHIC MEMBRANOUS GLOMERULONEPHRITIS AND IN CIDP- ASSOCIATED GLOMERULONEPHRITIS. (29th May 2021) - Salama, Alan; Fehmi, Janev; Antonelou, Marilina; Barratt, Jonathan; Ashman, Neil; Carr, Aisling; Reilly, Mary; Keddie, Stephen; Querol, Luis; Pikkuoeura, Sonja; Cortese, Andrea; Delmont, Emilien; et al.
Abstract: Background and Aims: Recently a number of antigens have been identified as pathogenic antibody targets in cases of primary membranous glomerulonephritis(MGN), including phospholipase A2 receptor (PLA2R), thrombospondin type 1 domain containing 7A(THSD7A), and NELL-1, while exostosin is found in secondary (lupus associated) MGN. However, other as yet undiscovered antigens are thought to exist. Although rare, there is a recognised association between chronic inflammatory demyelinating polyneuriopathy (CIDP) and nephrotic syndrome. Method: We investigated the link between CICP and MGN and the associations with Contactin-1(CNTN1), a node of Ranvier neuronal protein, as a potential common autoantigen, by immunohistochemistry, RT-PCR and proteomic analysis of isolated glomeruli. We tested sera from 468 patients with suspected immune-mediated neuropathies, 295 with idiopathic MGN, and 210 disease controls, for CNTN1 antibodies. Results: We describe a series of 16 patients, all presenting with CIDP, nephrotic syndrome due to MGN, and with circulating and deposited anti-contactin-1 (CNTN1) antibodies (IgG4 predominant in those tested) in the kidney. The onset and resolution of both disorders had a close temporal relationship, and the majority of cases were resistant to first-line therapies typically employed for inflammatory neuropathies, but achieved a good outcome with non-standard treatment. Importantly, four (1.4%) further patients with isolated MGN identified from a serum bank of 295 idiopathic MGN patients with no CIDP were also positive for anti-CNTN1 antibodies. CNTN1 protein was detected by mass spectroscopy within glomeruli from patients with CNTN1 antibodies, but not in healthy kidney or anti-PLA2 R associated MGN. CNTN1 mRNA was found in renal cortical tissue. Conclusion: These data provide evidence that CNTN1 antibodies precipitate both autoimmune neuropathy and MGN. The temporal correlation of these disorders, as well as the presence of CNTN1 protein and antibodies in both peripheral nerve and diseased glomeruli, supports a common antibody-mediated pathological process, and defines a new antigenic target in MGN. CNTN1 antibodies have diagnostic and therapeutic relevance, and may additionally serve as a means of monitoring disease activity in both conditions. Other factors may explain presentation with isolated neurological disease or MGN.